2020
DOI: 10.21203/rs.3.rs-78107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood Overweight and Obesity Among the Saudi Population: A Case-Control Study Among School Children

Abstract: BackgroundChildhood obesity is a global public health concern with major consequences. In Saudi Arabia, the percentage of children who are overweight or obese have significantly increased in the past 2 decades, raising concerns about the physical and psychosocial consequences of this burden. This study aimed at investigating the different risk factors contributing to childhood obesity in Saudi Arabia.Methods A case-control study was conducted among 492 school children (246 overweight/obese cases and 246 normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the present study, relatively younger HCWs (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and Master holders were more concerned about COVID-19. This might be explained by their lesser experience.…”
Section: Discussionmentioning
confidence: 50%
“…In the present study, relatively younger HCWs (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and Master holders were more concerned about COVID-19. This might be explained by their lesser experience.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, prevalences of smoking (42.2% versus 28.4%, p<0.01), excess weight (83.6% versus 70.6%, p<0.01), DM (16.3% versus 10.3%, p<0.05), and HT (23.2% versus 11.2%, p<0.001) were all higher in the hypertriglyceridemia group in another study (38). On the other hand, the prevalences of hyperbetalipoproteinemia were similar both in the hypertriglyceridemia (200 mg/dL and higher) and control groups (18.9% versus 16.3%, p>0.05, respectively) in the above study (38). Similarly, plasma LDL values increased just up to the plasma TG value of 200 mg/dL but no more in another study (39).…”
Section: Discussionmentioning
confidence: 81%
“…The relationships between excess weight, increased BP, and higher plasma TG values were described in the metabolic syndrome, extensively (37), and clinical manifestations of the syndrome include obesity, hypertriglyceridemia, hyperbetalipoproteinemia, HT, insulin resistance, and proinflammatory and prothrombotic states (37). Similarly, prevalences of smoking (42.2% versus 28.4%, p<0.01), excess weight (83.6% versus 70.6%, p<0.01), DM (16.3% versus 10.3%, p<0.05), and HT (23.2% versus 11.2%, p<0.001) were all higher in the hypertriglyceridemia group in another study (38). On the other hand, the prevalences of hyperbetalipoproteinemia were similar both in the hypertriglyceridemia (200 mg/dL and higher) and control groups (18.9% versus 16.3%, p>0.05, respectively) in the above study (38).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, in Riyadh, Aljassim and Jradi (38) found that 40.24% of parents had incorrect perception regarding their actual children's weight. Also in Abha City, Saudi Arabia, Al-Qahtani et al (55) found that most parents did not know the ideal weight for their children, and 57.6% of the parents of overweight or obese children were unaware that their children were overweight, and parents depended mainly on body shape for their perception of their child's weight.…”
Section: Discussionmentioning
confidence: 93%